PELATIHAN PENYELENGGARAAN JENAZAH BAGI GENERASI Z DI DESA BINCAU MARTAPURA KALIMANTAN SELATAN: PELATIHAN PENYELENGGARAAN JENAZAH BAGI GENERASI Z DI DESA BINCAU MARTAPURA KALIMANTAN SELATAN - Masruddin; Maulida Hayatina; Sahrahman; M. Miftah Arief; Miftah Farid; Suhar; Raihanah (LPPI UMN AL WASHLIYAH, 2026)
This community service activity is motivated by the limited understanding of Generation Z regarding the proper Islamic procedures for funeral management in Bincau Village, Martapura, South Kalimantan. The objective of this program is to enhance participants’ knowledge and practical skills in performing fardhu kifayah obligations, particularly in bathing, shrouding, and performing funeral prayers for the deceased. The implementation method employed an educative-participatory approach, including lectures, demonstrations, and hands-on practice, involving 60 youth participants. The results indicate a significant improvement in both conceptual understanding and practical competencies of the participants in all stages of funeral management, as evidenced by their ability to correctly perform bathing, shrouding, and funeral prayer procedures in accordance with Islamic teachings. Furthermore, the activity fostered increased religious awareness and social responsibility among Generation Z toward communal obligations. In conclusion, this training is effective in strengthening the religious competencies of young people and is recommended to be conducted sustainably to support community religious capacity building..